Study of tool wear characteristics while machining mono and graphite reinforced hybrid zinc - aluminium-based MMCs. (20th May 2021) - Marigoudar, Rajaneesh N.; Shashidhar, P.S.; Kanakuppi, Sadashivappa; Dharmendra, B.V.; Manjunatha, T.S.
The effect of graphite addition to conventional composites and making it hybrid for better machinability is the motto behind this work. Here, ZA43+SiC mono composite and ZA43+SiC+graphite hybrid composite are machined under dry condition. Machining is executed using commercially available coated carbide SNMG 090308 tool. Cutting variables viz. machining speed, feed rate and depth of machining are varied and for each machining trial fresh cutting edge is used. Tool damage is measured while machining both the categories of materials and are compared. It is noticed that the hybrid composite causes less damage in comparison with mono composite. The reason may be due to powdered graphite present in the composite which is responsible for reduction in the friction. Graphite being solid lubricant prevents tools getting abraded by the hard workpiece and promotes easy machinability. Statistical analysis done on the results gives the details about most influencing variable to the machining process. The tool wear during composite machining is greatly influenced by machining speed and feed. Optimum machining parameters can be drawn considering material composition for less tool wear condition.